Capacity of English NHS hospitals to monitor quality in infection prevention and control using a new European framework: a multi-level qualitative analysis. - Iwami,M; Ahmad,R; Castro,Sanchez E; Birgand,G; Johnson,AP; Holmes,AH (BMJ Open, 2017)
Objective: (1) To assess the extent to which current English national regulations/policies/guidelines and local hospital practices align with indicators suggested by a European review of effective strategies for infection prevention and control (IPC); (2) to examine the capacity of local hospitals to report on the indicators and current use of data to inform IPC management and practice. Design: A national and local-level analysis of the 27 indicators was conducted. At the national level, documentary review of regulations/policies/guidelines was conducted. At the local level: a) documentary review of 14 hospitals to determine the capacity to report on performance; b) qualitative interviews with three senior managers from five hospitals and direct observation of hospital wards to identify gaps in use of these indicators to improve IPC management and practice.Setting: Two acute English National Health Service (NHS) trusts and one NHS foundation trust (14 hospitals).Participants: Three senior managers from five hospitals for qualitative interviews.Primary and secondary outcome measures: As primary outcome measures, a ‘Red-Amber-Green’ (RAG) rating was developed reflecting how well the indicators were included in national documents or their availability at local organisational level. The current use of the indicators to inform IPC management and practice was also assessed. Secondary outcome measure includes the assessment of gaps across national and local levels by comparing the RAG rating results.ResultsNational regulations/policies/guidelines largely cover the suggested European indicators. The ability of individual hospitals to report some of the indicators at ward level varies across staff groups, which may mask required improvements. A reactive use of staffing-related indicators was observed rather than the suggested prospective strategic approach for IPC management.ConclusionsFor effective patient safety and infection prevention in English hospitals, ro